KONSEP IMPLEMENTASI PROFIL PELAJAR PANCASILA SEKOLAH DASAR DALAM PERSPEKTIF FILSAFAT KONTRUKTIVISME - Sarda Nuria Amiril; Ela Irnanda; Haidir; Yanti Fitria; Yeni Erita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Education in Indonesia has the responsibility to shape students' character in accordance with Pancasila values. This research aims to explain how the implementation of the Pancasila profile in elementary schools in the view of constructivist philosophy can be applied effectively to develop students' character based on Pancasila values. Constructivism philosophy is the theoretical basis for a learning approach that places students as agents of knowledge formation. The method used in this research is library research using a philosophical approach (analyzing the flow of constructivist philosophy on the profile of Pancasila Independen students). The data collection technique used is a documentation technique which is carried out by collecting data sourced from books in libraries and the internet, as well as articles and journals related to various writings in research. The results of this research show that the profile of Pancasila students is very in line with the constructivist philosophical theory which encourages teachers and students to build their own knowledge. The learning process is emphasized to create innovation that can motivate students to build their own learning experiences according to conditions. This Pancasila student profile emphasizes student-centered learning (student center), the teacher is no longer the center of learning but becomes a facilitator who helps facilitate students to explore their own knowledge, choose a learning style that suits them, giving complete freedom to students to be able to foster a brave, confident, independent and disciplined character.